Transforming missions : mission strategy and cyber space. Research on the use of cyber space in transforming the mission of the South Korean church in 21st century - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.